CHLORINE STABLE ISOTOPES IN CARBONATITES: EVIDENCE FOR ISOTOPIC HETEROGENEITY IN THE MANTLE - Eggenkamp H.G.M.; Koster van Groos A.F. (My University, 1997)
Eight carbonatite samples were analysed for δ37Cl and for δ18O and δ13C. The results show that unaltered carbonatites have δ37Cl ratios between −0.8 and +0.1‰. Because the whole mantle δ37Cl value is approximately +4.7‰, chlorine for carbonatite is anomalously light. Although it is possible that the source regions for carbonatites represent isotopic anomalous mantle and may reflect contamination by a crustal component, our preferred explanation is that the processes resulting in the accumulation of carbonatite magma cause fractionation of chlorine isotopes.